(+)-Usnic Acid-induced Myocardial Toxicity in Rats. (April 2015) - Yokouchi, Yusuke; Imaoka, Masako; Niino, Noriyo; Kiyosawa, Naoki; Sayama, Ayako; Jindo, Toshimasa
(+)-Usnic acid (UA) has been known to be a strong uncoupler, and mitochondrial and endoplasmic reticulum (ER)–related stresses are suggested to be involved in the mechanism of hepatotoxicity. However, it has not been clarified whether UA causes toxicity in other mitochondria-rich organs such as the heart. We elucidated whether UA induces cardiotoxicity and its mechanism. UA was orally administered to rats for 14 days, and laboratory and histopathological examinations were performed in conjunction with toxicogenomic analysis. As a result, there was no alteration in blood chemistry, whereas cytoplasmic rarefaction of myocardium was observed microscopically. This finding corresponded to the swollen mitochondria observed ultrastructurally. Immunohistochemically, expression of prohibitin, indicating mitochondrial imbalance, increased in the sarcoplasmic area. Toxicogenomic analysis highlighted the upregulation of gene groups consisting of oxidative stress, ER stress, and amino acid limitation. Interestingly, the number of upregulated genes was larger in the amino acid limitation-related gene group than that in other groups, implying that amino acid limitation might be one of the sources of oxidative stress, not only mitochondria and ER-originated stresses. In conclusion, the heart was manifested to be one of the target organs of UA. Mitochondrial imbalance with complex stresses may be involved in the toxic mechanism.